2017
DOI: 10.1136/bcr-2016-217855
|View full text |Cite
|
Sign up to set email alerts
|

Use of cabergoline for the management of persistent Cushing’s disease in pregnancy

Abstract: Cushing's disease (CD) is rare during pregnancy and is associated with significant maternal and fetal complications. It is important to control hypercortisolism during pregnancy, either surgically or medically, for a successful maternal and fetal outcome. We report a patient with recurrent CD who was treated with low-dose cabergoline (CAB) for persistent hypercortisolism throughout pregnancy. A 36-year-old woman was diagnosed with CD at the age of 23. She underwent trans-sphenoidal surgery with initial complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Its innocuous profile during gestation has been confirmed with an increasing number of uneventful pregnancies (mostly for prolactinomas) ( 60 ). Efficacy and safety of cabergoline in CD in pregnancy is also supported by a number of case reports ( 61 63 ).…”
Section: Medications Approved For Other Indications Than CDmentioning
confidence: 75%
“…Its innocuous profile during gestation has been confirmed with an increasing number of uneventful pregnancies (mostly for prolactinomas) ( 60 ). Efficacy and safety of cabergoline in CD in pregnancy is also supported by a number of case reports ( 61 63 ).…”
Section: Medications Approved For Other Indications Than CDmentioning
confidence: 75%
“…At doses of 1.5-5 mg/week a response is expected to be around 30-50% in patients with mild or moderate disease (24). Cabergoline is only advantageous for CD in pregnancy where therapeutic options are otherwise limited (27,28). However, the most experience in CS in pregnancy is with metyrapone, which is generally well tolerated, but hypertension and preeclampsia have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine receptor (DR) expression in ACTH-secreting PAs has been described [ 17 ]. While several case reports have demonstrated that ACTH-secreting PAs may respond to treatment with Cabergoline [ 18 , 19 , 20 , 21 , 22 , 23 ], the results in larger cohorts of patients bearing such tumors still remain controversial [ 24 , 25 ]. However, administration of dopamine agonists is worth considering as an option to treat these tumors [ 13 , 14 ], and a clinical trial on Cabergoline treatment in corticotroph PAs (Mumbai, India ( (accessed on 6 November 2021)) [ 26 ]; trial identifier: NCT00889525; Table 1 ) has been initiated.…”
Section: Emerging Targeted Treatment Strategies At the Molecular Levelmentioning
confidence: 99%